'An Extremely Useful Invention': Edison's electric pen and the unravelling of old and new media. (August 2019) - Unwin, Peter
Using Edison's electric pen as a case study, this article examines the role of media narratives in determining the ways in which a new medium is finally judged a success or failure. By challenging the narrative of the electric pen as a failed technology, it maintains that oppositional criteria such as new/old, winner/loser and successful/obsolete are counterproductive to a meaningful understanding of technical media. Instead, this article seeks to reposition and reappraise the electric pen, not as a study in failure and obsolescence, but as a site for the implementation of powerful cultural narratives that helped to define individuality and human agency in the beginnings of the modern age.